2005
DOI: 10.1104/pp.105.063263
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Physiological Architecture of Early Vigor in Aegilops tauschii, the D-Genome Donor of Hexaploid Wheat. A Quantitative Trait Loci Analysis

Abstract: Plant growth can be studied at different organizational levels, varying from cell, leaf, and shoot to the whole plant. The early growth of seedlings is important for the plant's establishment and its eventual success. Wheat (Triticum aestivum, genome AABBDD) seedlings exhibit a low early growth rate or early vigor. The germplasm of wheat is limited. Wild relatives constitute a source of genetic variation. We explored the physiological and genetic relationships among a range of early vigor traits in Aegilops ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 59 publications
3
54
1
Order By: Relevance
“…As described in the introduction of this article, it is often shown that there is a balance between both cell area and cell number in plants (Ter Steege et al, 2005;Ferjani et al, 2007). In the first general analysis, we found that it was not the case in the whole population studied here: Both variables were positively correlated with final leaf 6 area, but there was no correlation between them.…”
Section: Relationships Between Leaf Area Epidermal Cell Number and mentioning
confidence: 51%
“…As described in the introduction of this article, it is often shown that there is a balance between both cell area and cell number in plants (Ter Steege et al, 2005;Ferjani et al, 2007). In the first general analysis, we found that it was not the case in the whole population studied here: Both variables were positively correlated with final leaf 6 area, but there was no correlation between them.…”
Section: Relationships Between Leaf Area Epidermal Cell Number and mentioning
confidence: 51%
“…Various studies carried out, e.g. by [30] and [8] indicate a positive correlation between the germination capacity and the early vitality of grain. The germination capacity depends closely on the external conditions accompanying the processes of grain setting and filling, grain storage conditions [31][32][33][34] as well as grain size [35].…”
Section: Discussionmentioning
confidence: 99%
“…Wild species related to bread wheat show remarkable genetic diversity essential to the improvement of the quality of cultivated plants. The D genome originating from A. tauschii is considered a potential donor of traits associated with the vigour of grain, including germination capacity [30,41,42]. The principal regions on D genome associated with grain germination provide a common location for the genes coding for D-type cyclins (1D) and cytochrome 450 genes (P450 gene family), spermitine synthase 1 (SPDSY 1) (7D), and protein synthase gene.…”
Section: Discussionmentioning
confidence: 99%
“…A negative relationship between cell number and cell size has been reported in cell cycle transgenic lines (Hemerly et al 1995) and in a population of recombinant inbred lines of Aegilops tauschii (Ter Steege et al 2005). The basis of these partial compensations are not known but they are probably under genetic control as the analysis of a population of recombinant inbred lines led to overlapping QTLs, with opposite effects for each couple of variables (Ter Steege et al 2005).…”
Section: Opposite Effects On Dynamics and Cellular Leaf Growth Variabmentioning
confidence: 99%